The Effect of Teacher Support Perception on Student Engagement in Students of SMAIT Al-Fityan School Gowa - Cahyani, Satifah; Razak, Ahmad; Akmal, Nur (Polteknik Ilmu Pemasyarakatan, 2025)
Student Engagement is the active involvement of students in academic activities. It is undeniable that there are still students who show a passive attitude in class, how students' perceptions of teacher support play a role in shaping changes in all aspects of participation in class. Therefore, this study aims to determine the effect of teacher support perceptions on student engagement in students. The method used in this study is a quantitative research method. The subjects in this study were 138 who were taken using the accidental sampling technique. The measuring instrument was student engagement and teacher support scale. The data in this study were analyzed using simple linear regression. The results of this study showed a significance value of 0.000, means that teacher support has an effect on student engagement in SMAIT Al-Fityan School Gowa students. The r value is 0.390 and the R Square value is 0.152, which means that teacher support has an effect of 15.2% on student engagement. The implications of this study are to contribute to developing knowledge related to teacher support and student engagement, in addition to providing guidelines for students, teachers, and schools in order to improve teacher support and student engagement in schools.